1990
DOI: 10.1136/jech.44.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular diseases in Chinese, Malays, and Indians in Singapore. I. Differences in mortality.

Abstract: Study objective-The aim ofthe

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
53
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(63 citation statements)
references
References 12 publications
9
53
0
1
Order By: Relevance
“…This finding is in accordance with previous findings [11,[15][16][17][18][19][20][21]. As in previous studies, adjustment for other traditional risk factors did not entirely account for the increased risk of IHD in this ethnic group [11,19].…”
Section: Discussionsupporting
confidence: 83%
“…This finding is in accordance with previous findings [11,[15][16][17][18][19][20][21]. As in previous studies, adjustment for other traditional risk factors did not entirely account for the increased risk of IHD in this ethnic group [11,19].…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, we have shown that increasing PBF in men and women, especially to levels beyond the overweight and obese cutoff points, was associated with higher levels of TC, LDL, TC/HDL, INS, and GLU and lower levels of HDL. Clearly, the classifications based on DEXAderived PBF in the present study showed that obesity was associated with increased risks of coronary heart disease and type 2 diabetes, as was shown earlier (13,15,26,29).…”
Section: Discussionsupporting
confidence: 52%
“…More than 50% of CAD associated death in India occurs before the patient reaches the age of 50 years (28) and 25% of myocardial infarction (MI) occur before the age of 40 years (29). Heart disease is occurring in Asian Indians 5-10 years before other ethnicities (30) because the CAD shows accelerated atherogenesis which results in higher premature morbidity and mortality (31). Since Asian Indians have a lower prevalence of conventional risk factors such as hypertension, hypercholesterolemia, obesity and smoking (8,13,32) it is important to explore the underlying causes of increased CAD prevalence.…”
Section: Risk Factorsmentioning
confidence: 99%